Role of STEVOR and its interacting partners in parasite virulence - Omelianczyk, Radoslaw Igor (Nanyang Technological University, 2020)
The genomes of Plasmodium spp. encode a number of different multigene families that are thought to play a critical role for survival. However, with the exception of the P. falciparum var genes, very little is known about the biological roles of any of the other multigene families. The stevor family includes about 40 genes and is therefore the smallest family of variant surface antigens in P. falciparum. While some of its members have been shown to interact with glycophorin C, some others are presented at the apical tip of merozoites where they are involved in invasion. However, much of the diversity within the family is still understudied. The first part of this work describes our efforts to identify STEVOR with novel binding properties to red blood cells. To this end, amino acid sequence alignment provided information about the diversity within the family. In order to cover the entire diversity within the stevor multigene family, a large subset of different STEVOR were expressed on the surface of mammalian cells or recombinantly in bacteria. We successfully identified one stevor with atypical binding behaviour to red blood cells, providing us with a lead candidate for further studies. The second part of this work describes efforts to develop a platform to study members of multigene families in P. falciparum. Using the recently developed Selection Linked Integration method, we have been able to activate the expression of a single member of a multigene family of our choice from its endogenous promoter. We characterize parasites expressing specific members of the var, rifin and stevor multigene families in terms of protein localization, function and epigenetic control mechanisms underlying their expression. We show that endogenous tagging of a PfEMP1 does not disrupt transport of the protein to the surface of the host red blood cell, suggesting that the protein transport is not altered by the knock-in method. Furthermore, knock-in of two previously described RIFIN causes the parasites to become resistant to natural killer cell killing, proving functionality of the proteins. Finally, knock-in of three different STEVOR highlights the diversity observed in this multigene family. Each of the proteins shows a different subcellular localization, with one being exposed in the surface of the infected red blood cell, one remaining within the Maurer’s Clefts and one being expressed as a truncation. Using microarray analysis, we gain new insights into the regulatory mechanisms within and between multigene families. We can show that knock-in of stevor causes monoallelic expression, suggesting mutual exclusive control within this family. In contrast, rifin do not appear to have any level of control mechanisms. Furthermore, we observe cross-talk between multigene families as expression from a genomic locus causes upregulation of some, but not all, adjacent genes. We show that similar observations have been reported previously, suggesting true interaction instead of artefacts introduced by the knock-in Finally, we studied intracellular interaction partners of STEVOR utilizing two independent approaches: co-immunoprecipitation and proximity labelling by BioID. We show that both the surface exposed and the Maurer’s Cleft resident STEVOR interact with unique subsets of proteins. While the surface exposed protein appears to be incorporated into the new permeability complex together with other small variant antigens, the other one is associated with lipid rafts within the Clefts.